2020
DOI: 10.1249/mss.0000000000002277
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Improves Video Game Performance: A Win–Win Situation

Abstract: Purpose Video gamers exceeding screen-time limits are at greater risk of experiencing health issues associated with physical inactivity. Demonstrating that exercise has positive effects on video game performance could promote physical activity among video gamers. We investigated the short-term effects of a single session of cardiovascular exercise on the performance of the popular video game League of Legends (LoL) and explored psychosocial mechanisms. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 36 publications
1
31
0
1
Order By: Relevance
“…Kari and Karhulahti (2016) also showed that 9% of elite esports players (from several esports genres) reported the main reason for being active was improving esports performance and 6% believed that integrating physical exercise in their training programmes has a positive effect on esports performance. Actually, recent studies highlighted the association between physical activity and increased esports performance (i.e., accuracy and objective fulfilment, and cognitive aspects of gaming) (de Las Heras et al, 2020;Toth et al, 2020). The fact that the current study included both elite and recreational virtual football players might be a reason to different perceptions to that question.…”
Section: Esports Practice and Physical Trainingmentioning
confidence: 90%
See 2 more Smart Citations
“…Kari and Karhulahti (2016) also showed that 9% of elite esports players (from several esports genres) reported the main reason for being active was improving esports performance and 6% believed that integrating physical exercise in their training programmes has a positive effect on esports performance. Actually, recent studies highlighted the association between physical activity and increased esports performance (i.e., accuracy and objective fulfilment, and cognitive aspects of gaming) (de Las Heras et al, 2020;Toth et al, 2020). The fact that the current study included both elite and recreational virtual football players might be a reason to different perceptions to that question.…”
Section: Esports Practice and Physical Trainingmentioning
confidence: 90%
“…Actually, esports players at elite levels of different esports genres have been reported to be physically active, which is against the empirical notion that esports players are inactive (Kari and Karhulahti, 2016;Trotter et al, 2020). Besides, exercise and physical activity might be important to increased esports performance (de Las Heras et al, 2020;Toth et al, 2020). With Portuguese esports scene rising (Fepodele, 2019)-with special emphasis in virtual football -, it is vital to know more about the physical activity levels of people engaged with esports and understand the relationship between esports practice, sedentary time and motivations for being physically active.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…De Las Heras et al exercised gamers using HIIT for 15 min at an RPE of 15.17 (0.34), which translates to working 'hard' or 'heavy'. 26 The average RPE for participants in the walking condition in this study was 10.5 (2.8), which translates to 'light' intensity effort. Interestingly, the RPE for gaming was higher than the RPE for the walking break.…”
Section: Exercise Intensitymentioning
confidence: 72%
“…Es común asociar videojuegos y sedentarismo, pero no es una relación correcta, como desmienten algunos estudios (Griffiths, 2002;De las Heras, et al 2020). Muchas empresas de videojuegos han apostado por levantar al jugador y obligarle a moverse más.…”
Section: Videojuegos Y Movimientounclassified